2015
DOI: 10.1111/imm.12453
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase activated receptor‐2‐mediated dual oxidase‐2 up‐regulation is involved in enhanced airway reactivity and inflammation in a mouse model of allergic asthma

Abstract: SummaryAirway epithelial cells (AECs) express a variety of receptors, which sense danger signals from various aeroallergens/pathogens being inhaled constantly. Proteinase-activated receptor 2 (PAR-2) is one such receptor and is activated by cockroach allergens, which have intrinsic serine proteinase activity. Recently, dual oxidases (DUOX), especially DUOX-2, have been shown to be involved in airway inflammation in response to Toll-like receptor activation. However, the association between PAR-2 and DUOX-2 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…This has been confirmed by ROS scavengers which attenuate allergen induced airway hyperresponsiveness and inflammation in various animal models of asthma (Nadeem et al, 2014b;Peh et al, 2015). Furthermore, different isoforms of NOX have been shown to regulate airway inflammation and hyperreactivity in both animal and human studies (Sutcliffe et al, 2012;Nadeem et al, 2014bNadeem et al, , 2015Voraphani et al, 2014). However, to the best of our knowledge, no study has investigated the effect of TLR-7 activation on NOX-2/NOX-4 signaling during allergic responses in a murine model of asthma.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This has been confirmed by ROS scavengers which attenuate allergen induced airway hyperresponsiveness and inflammation in various animal models of asthma (Nadeem et al, 2014b;Peh et al, 2015). Furthermore, different isoforms of NOX have been shown to regulate airway inflammation and hyperreactivity in both animal and human studies (Sutcliffe et al, 2012;Nadeem et al, 2014bNadeem et al, , 2015Voraphani et al, 2014). However, to the best of our knowledge, no study has investigated the effect of TLR-7 activation on NOX-2/NOX-4 signaling during allergic responses in a murine model of asthma.…”
Section: Discussionmentioning
confidence: 85%
“…Emerging evidence suggests that NOX-derived ROS contribute to diverse signaling processes, including TLR-induced inflammation (Amatore et al, 2015;Nadeem et al, 2015;Yang et al, 2013). For example, it has been demonstrated that NOX-2 plays an important role in TLR-2 as well as TLR-3 dependent inflammatory responses and antimicrobial activity against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that autophagy is essential for IL-13 to modulate ROS and mucus formation in epithelial cells during asthma (38). A study suggested that proteinaseactivated receptor 2 (PAR-2) is involved in airway inflammation regulation through oxidative stress, leading to increased DUOX-2/ROS pathway activation in airway epithelial cells (39). In human bronchial epithelial cells, lack of glutathione S-transferase Mu 1 (GSTM1) enhances ozone-induced IL-8 production because of ROS generation and subsequent NF-κB activation (40).…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…PAR-2 mediated DUOX-2 and ROS in airway epithelial cells in a cockroach allergen mice model. However, ENMD-1068, a small molecule antagonist of PAR-2, can inhibit DUOX-2 and ROS in allergic mice (39). NLRP3 inflammasome assembly is activated by mitochondrial ROS, which consequently induces IL-1β production and release (36).…”
Section: Inflammatory Cellsmentioning
confidence: 99%
See 1 more Smart Citation